Lateralized Effects of Unilateral Thalamotomy and Thalamic Stimulation in Patients with Essential Tremor - Kim, Mi J. (The Korean Movement Disorder Society, 2011)
BACKGROUND AND PURPOSE: Stereotactic thalamotomy has been an effective surgical procedure in the treatment of medically refractory essential tremor (ET), however, little is known about the bilateral effects of unilateral ventralis intermedius (Vim) thalamotomy and Vim deep brain stimulation (DBS). We studied the lateralized effects of unilateral Vim thalamotomy and Vim DBS in ET patients. METHODS: Vim thalamotomy was performed in 6 patients and Vim DBS in 6. Patients were evaluated preoperatively and at 3 and 6 months postoperatively using the Clinical Rating Scale for Tremor (CRST). RESULTS: The contralateral Part A (tremor localization/severity rating) and Part B (specific motor tasks/function rating) subscores, and axial subscores of CRST significantly improved after unilateral Vim thalamotomy or Vim DBS. On the side ipsilateral to surgery, ET patients demonstrated no significant improvements in the Part A and Part B subscores of CRST. The Part C (functional disabilities resulting from tremor) subscores and total scores of CRST were significantly improved after surgery. CONCLUSIONS: Vim thalamotomy and DBS may be equally effective for the management of contralateral and axial tremor in ET patients, but both interventions may not improve tremor on the side ipsilateral to surgery.